Filogenia, biogeografia e ecologia de ácaros Opilioacarida With 1904 (Acari: Parasitiformes) - Bernardi, Leopoldo Ferreira de Oliveira (2015)
The order Opilioacarida (Arachnida; Parasitiformes) is considered by many acarologists to be a rare group that retains primitive features, which can be an important point for understanding the evolution of the entire line of Parasitiformes. Despite the relevance of the order, there are few studies aimed at understanding more about their phylogeny and ecology. This thesis presents, for the first time, a phylogeny for the 9 genera of order (Salfacarus, Panchaetes, Indiacarus, Phalangiacarus, Opilioacarus, Amazonacarus, Caribeacarus, Brasilacarus and Neocarus) and for as yet undescribed species from Australia and Brazil. These analyzes were based on parsimony criteria of morphological data. With the results it was observed that genera Neocarus, Caribeacarus and Brasilacarus are paraphyletic in relation to Amazonacarus; Salfacarus has no unique features, so it can be considered a separate genus of Panchaetes; Indiacarus and Phalangiacarus were considered synonymous with Opilioacarus. Thus, only Panchaetes, Opilioacarus and Neocarus were considered valid genera. Furthermore, for some undescribed Brazilian species, a new genus is proposed (Tupiniacarus gen. nov.), that shows morphological similarities with Australian species. The other species found in Brazil were considered as belonging to the genus Neocarus and are described in one of the chapters of the thesis. A brief discussion of sexual dimorphism, from observations of these changes in the external morphology of the species Opilioacarida is presented. After morphological analysis and based on the new proposed classification for the Opilioacarida, we designed a study on the distribution of potentially suitable habitats for each genus as well as testing the possibility of niche overlap among Panchaetes, Opilioacarus, Neocarus, the new proposed genusof Brazilian specimens and a group of still undescribed Australian species. For this, maximum entropy and niche modeling methods were used. The results showed that regions with greater environmental suitability are focused primarily in the intertropical region. In addition, although locals where genera are found in sympatryare rare, there are overlaps in potential distribution and among the conditions of the occupied habitats. Thus, there is overlap among the environmental niches occupied by the genera. However, phylogenetically close generado not always present higher similarity among their niches and potentially environmentally appropriate areas.